PRODUCTION OF BETA-GALACTOSIDASE IN SUBMERGED MEDIA BY ASPERGILLUS ORYZAE, PTCC 5 163 (Journal of Sciences, Islamic Republic of Iran)
Different compositions of liquid media were used for their efficacy in the production of beta-galactosidase by Aspergillus oryzae in submerged fermentation. Enzyme production was improved by switching from lactose-based media to soybean meal- and wheat bran-based media. Further improvement was made when the soybean meal medium was supplemented with sodium nitrate and magnesium sulfate. Results also indicate that fungal extracellular beta-galactosidase production occurs concomitantly with growth on complex media but not on lactose- based media. The effectiveness of Tween 80 on beta-galactosidase activity was found to depend on the type of the medium used